2015
DOI: 10.1108/jme-05-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

“I’ll do this no matter if I have to fight the world!”

Abstract: Purpose – The purpose of the paper was to explore students’ learning experiences in culturally diverse urban higher education environments. Design/methodology/approach – The project used an action research method approach with a mixed-method collection of data. The data consist of a survey of undergraduate students from the two different faculties, business and science, in two London institutions (n = 393) and ten focus groups (consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The significance of these different student journeys and the need for universities to support the successful transition of its students as part of that journey has been noted by others (Bamford et al, 2015). The cultural plurality of the educational space adds an additional dimension to the transition process that individual practitioners seem unable to respond to without an institutional framework.…”
Section: Institutional Deficit Modelmentioning
confidence: 95%
See 3 more Smart Citations
“…The significance of these different student journeys and the need for universities to support the successful transition of its students as part of that journey has been noted by others (Bamford et al, 2015). The cultural plurality of the educational space adds an additional dimension to the transition process that individual practitioners seem unable to respond to without an institutional framework.…”
Section: Institutional Deficit Modelmentioning
confidence: 95%
“…This a view is supported by Meeuwisse et al (2010) who found that for students from minority ethnic backgrounds and those who are first generation in HE, the quality of the interactions was strongly indicative of academic progress and success. Bamford et al (2015) findings support the embedding of experiential learning activities into the curriculum to build the community dynamic of the curriculum.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations